Fungsi Manajerial Kepala Sekolah dalam Mewujudkan Program Keagamaan - Muhammad Ali (Studia Manageria, 2020)
The purpose of this study was to determine the planning function, the organizing function, the mobilizing function, the realized religious program, and the obstacles to the implementation of religious programs in Terawas State High School. This study usesa descriptive qualitative approach, with data collection tools in the form of observation, interviews, and documentation. While the analysis of the data uses an interactive descriptive analysis of the Miles and Heberman concepts through triangulation. Theanalysis in this study revealed that: (1) Institutionally the principal has performed a managerial role as a figure who always supports activities, exposes each activity, and a role as an entrepreneur in developing religious programs through breakthroughsand big ideas. (2) The religious program has been running well, it is marked by the pioneering work of the Terawas State High School in the use of Muslim clothing (Jilbab) to become mandatory clothing in the school environment. (3) The realization of religious programs in the Terawas State High School is a serious effort together and positive support from all components in the school. (4) The still limited awareness of some students of the importance of fostering the values of faith and piety becomes an obstacle to the implementation of religious programs in Terawas State High Schools